2020
DOI: 10.1038/s41467-019-14185-z
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic TET3 contributes to type-2 diabetes by inducing the HNF4α fetal isoform

Abstract: Precise control of hepatic glucose production (HGP) is pivotal to maintain systemic glucose homeostasis. HNF4α functions to stimulate transcription of key gluconeogenic genes. HNF4α harbors two promoters (P2 and P1) thought to be primarily active in fetal and adult livers, respectively. Here we report that the fetal version of HNF4α is required for HGP in the adult liver. This isoform is acutely induced upon fasting and chronically increased in type-2 diabetes (T2D). P2 isoform induction occurs in response to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…However, TLB effectively enhanced the glucose tolerance of KK-Ay mice. Likewise, ITT is implemented to test the body's sensitivity to exogenous insulin (Da et al, 2020). The results showed that KK-Ay mice had a low sensitivity to exogenous insulin, that is why the mice kept a high level of blood glucose after injection of recombinant human insulin, in keeping with the previous studies (Ogiwara et al, 2018).…”
Section: Discussionsupporting
confidence: 66%
“…However, TLB effectively enhanced the glucose tolerance of KK-Ay mice. Likewise, ITT is implemented to test the body's sensitivity to exogenous insulin (Da et al, 2020). The results showed that KK-Ay mice had a low sensitivity to exogenous insulin, that is why the mice kept a high level of blood glucose after injection of recombinant human insulin, in keeping with the previous studies (Ogiwara et al, 2018).…”
Section: Discussionsupporting
confidence: 66%
“…Interestingly, two new studies in mice showed that increased translation of two proteins in the liver, TET3 and HNF4a, results in increased production of blood glucose and insulin. Specifically, it was shown that abnormal protein signaling of TET3 contributes to the development of fibrosis in the liver [185,186]. Based on these data it has been proposed that targeting the TET3 and HNF4a proteins could reverse type-2 diabetes and liver fibrosis.…”
Section: The Mtorc1 Signaling Pathway In Metabolic and Inflammatory Dmentioning
confidence: 99%
“…The evolutionarily conserved transcription factor hepatocyte nuclear factor 4 alpha (HNF4α) plays an important role in promoting hepatic glucose production and regulating energy balance [ 13 ]. In a previous study, Huang and associates reported that the DNA demethylase TET3 binds to and demethylates the P2 promoter of HNF4α, leading to increased transcription of the P2 isoform of HNF4α (known as HNF4α-P2) and a consequently abnormally augmented hepatic glucose production that underlies the chronic hyperglycemia in type 2 diabetes [ 14 ]. More recently, the same group, using mouse models and human primary hepatocytes, demonstrated that metformin, at clinically relevant doses, suppresses hepatic glucose production by activating a conserved regulatory pathway encompassing let-7, TET3, and HNF4α-P2 [ 15 ].…”
Section: Novel Molecular Targets Involved In Glycemic Controlmentioning
confidence: 99%